Pelatihan Manajemen Pariwisata Berkelanjutan untuk Meningkatkan Kapasitas Pokdarwis Desa Bojong Koneng, Kabupaten Bogor - Yesi Pandu Pratama Wibowo DC; Rachmawati Dewi; Lamria Raya Fitriyani (Jurnal Pengabdian Masyarakat Charitas, 2026)
Bojong Koneng Village, Bogor Regency, has strong natural tourism potential, including Bukit Daolong, Bukit Silala, and Air Terjun Bidadari, which have developed as alternative trekking destinations attracting increasing visitors. Based on the Tourism Area Life Cycle (TALC), the village is at the Involvement stage, marked by growing visitor numbers and emerging community participation, but without a formally established Tourism Awareness Group (Pokdarwis). Tourism management has relied mainly on Karang Taruna. This community service program aimed to strengthen the capacity of Karang Taruna members as prospective Pokdarwis by enhancing their understanding of tourism management, Pokdarwis roles, and medium-term destination development strategies. Conducted on 10 November 2025 with 15 participants, the training applied interactive methods such as discussions, simulations, and pre–post tests. Results showed a 17.59% increase in participants’ knowledge and the successful design of integrated trekking-based tourism packages. The program supports SDGs 8, 11, and 12 and produced a practical management module currently undergoing IPR registration.